Ketangguhan Kota Semarang dalam Menghadapi Bencana Banjir Pasang Air Laut (Rob) - Ria Erlani; Widyasari Her Nugrahandika (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
Climate change becomes a big problem for Semarang City. One of the effects of climate change in Semarang City is the tidal flooding (rob). The existing tidal flooding is a consequence of the increase of land surface subsidence and the rise of sea level. It affects many aspects of life and livelihood of the society, including on physical, social, economic, environmental, and health aspects. In 2012, MercyCorps and ARUP declared Semarang City as one of the cities resilience to climate change. In 2014, Semarang City became the only city in Indonesia to take part in the 100 Resilient Cities program (100 RC). This research aims to identify the measures that have been done by stakeholders in facing tidal flood and to measure the resilience level of Semarang City in encountering tidal flood. The location of this research covers the area along the coast of Semarang City which stretches from west to east as far as 13.6 km. This research uses quantitative-qualitative deductive method. Based on the analysis result, the measures that have been done by the stakeholders in Semarang City resulted in “medium” resilience level against tidal flood. This implies that Semarang City has not yet been resilient in facing tidal flood. However, the existence of the 100RC program has made Semarang City Government work harder to achieve the goal of the 100RC project, which is Semarang City that is resilient in facing all challenges, both in the form of shock and stress.